Squamous cell carcinoma development in Fanconi anemia patients who underwent hematopoietic stem cell transplantation. (7th April 2020) - Anak, Sema; Yalman, Nevin; Bilgen, Hülya; Sepet, Elif; Deviren, Ayhan; Gürtekin, Başak; Tunca, Fatih; Başaran, Bora
Abstract: We examined SCC development of 24 FA patients, who received HSCT from HLA‐matched relatives. In our BMT center, we applied low‐dose CY + LFI + ATG (n:13) as conditioning regimen for FA patients between 1992 and 1999, and CY + BU + ATG (n:11) between 1999 and 2002. The aim of this study was to investigate SCC development after HSCT and examine features of the follow‐up patients. The 10‐year overall survival (OS) of the group with LFI + regimen was 43%, whereas the group without LFI regimen was 60%. There was a statistically significant relationship between infections (viral/bacterial) and overall survival (Fisher's Exact test P  < .001). Five out of 13 long‐term (>1 year) surviving patients developed SCC in the HNSCC (n:4) and esophagus (n:2) region (a patient with oral SCC developed a second primary esophageal SCC). The SCC rate in our FA patients was 38%, four of the SCC patients were transplanted with irradiation used conditioning regimens, three of them had acuteGvHD (Grade II‐III), only one developed chronic GvHD. The interval between HSCT and SCC diagnosis was median 13 (range 6‐18) years, the age for the development of cancer was median 21 (range 15‐32) years. Survival after SCC was low, median 6 months (range 6‐12), due to delayed SCC diagnosis, tumor progression under therapy and treatment‐related toxicities of the usually reduced RT and/or CT.